1997
DOI: 10.1046/j.1365-2141.1997.4203237.x
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the biology of Philadelphia‐chromosome‐positive acute lymphoblastic leukaemia using a combination of May‐Grünwald‐Giemsa staining and fluorescence in situ hybridization techniques at the single cell level

Abstract: It is sometimes difficult to discriminate chronic myeloid leukaemia (CML) in lymphatic blast crisis from Ph‐chromosome positive acute lymphoblastic leukaemia (ALL). Previous studies have suggested that ALL is restricted to the lymphatic lineage only, whereas CML involves all cell lineages. In four cases of Ph‐positive ALL we combined the standard May‐Grünwald‐Giemsa staining with FISH at the single cell level and were able to demonstrate that  98% of lymphatic blasts carried the Philadelphia chromosome. Erythr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…These data add to previous studies by who observed a more favourable outcome in Ph þ ALL with multilineage involvement than in similar patients in whom the genetic marker was confined to lymphoid blasts. As Haferlach et al (1997) pointed out, these findings are apparently at variance with a previous study by our group (Cuneo et al, 1994), describing a poor prognosis in Ph þ ALL with a minor myeloid component, consisting of 5-15% blast cells with morphologic and cytochemical features of the granulocytic lineage.…”
Section: Department Of Paediatric Oncology M Dü R K E N and Haematolcontrasting
confidence: 56%
See 2 more Smart Citations
“…These data add to previous studies by who observed a more favourable outcome in Ph þ ALL with multilineage involvement than in similar patients in whom the genetic marker was confined to lymphoid blasts. As Haferlach et al (1997) pointed out, these findings are apparently at variance with a previous study by our group (Cuneo et al, 1994), describing a poor prognosis in Ph þ ALL with a minor myeloid component, consisting of 5-15% blast cells with morphologic and cytochemical features of the granulocytic lineage.…”
Section: Department Of Paediatric Oncology M Dü R K E N and Haematolcontrasting
confidence: 56%
“…LINEAGE INVOLVEMENT AND PROGNOSIS IN Ph CHROMOSOME POSITIVE ACUTE LYMPHOBLASTIC LEUKAEMIA Haferlach et al (1997) raised an interesting problem concerning the correlation of lineage involvement and prognosis in Philadelphia chromosome positive acute lymphoblastic leukaemia (Ph þ ALL). By combining May-Grunwald-Giemsa staining with fluorescence in situ hybridization (FISH), the authors provided unequivocal evidence for the presence of BCR/ABL fusion in lymphoid blasts and in granulocytic cells in two patients with a favourable clinical course.…”
Section: Department Of Paediatric Oncology M Dü R K E N and Haematolmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the presence of BCR-ABL1 + myeloid cells in B-ALL patients (23,24). These observations have been attributed to the presence of the BCR-ABL1 translocation in a multipotent progenitor cell, capable of both lymphoid and myeloid differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The simultaneous analysis of hybridization pattern and cell morphology proved to be an efficient method for the study of lineage involvement in hemopoietic neoplasms 8,9,17 and unequivocally showed that the target stem cell for leukemogenesis in this case of t(4;11) leukemia retained the capability to differentiate in vivo along the lymphoid and granulocytic pathways.…”
Section: Figurementioning
confidence: 99%